MUSCLE FIBER DIAMETER AND FAT TISSUE SCORE IN QUAIL (Coturnix-coturnix japonica L) MEAT AS AFFECTED BY DIETARY TURMERIC (Curcuma longa) POWDER AND SWANGI FISH (Priacanthus tayenus) MEAL - Kartikayudha, W.; Isroli, I.; Suprapti, N.H.; Saraswati, T.R. (Diponegoro University, 2013)
The objectives of this study were evaluate the dietary turmeric powder and swangi fish meal onsize of muscle fiber diameter and fat tissue score of major pectorales and semimembranosus of quailmeat. Research was conducted based on 2x3 of factorial completely randomized design, in which thefirst factor was 2 types of diet, i.e. RA : standard diet; RB : 85% standard diet + 15% swangi fish meal,and the second factor was 3 levels of period time of turmeric powder addition, i.e. P0 : without turmericpowder; P1 : turmeric powder 54 mg/quail/day was given since quail age 210 days old; P2 : turmericpowder 54 mg/quail/day was given since quail age 14 days old. Difference of means between treatmentgroups were analyzed by Duncan’s Multiple Range Test in 95% significance level. The results showedthat combined treatment of tumeric powder with RA (P0 : 2.33 μm; P1 : 3.06 μm; P2 : 2.98 μm) and RB(P0 : 2.22 μm; P1 : 3.12 μm; P2 : 2.92 μm) increased (P<0.05) muscle fiber diameter on majorpectorales significantly. Muscle fiber diameter on semimembranosus were increased (P<0.05) bycombined treatment of tumeric powder with RA (P0 : 2.83 μm; P1 : 3.50 μm; P2 : 3.24 μm) and RB (P0= 2.85 μm; P1 = 3.28 μm; P2 = 3.33 μm). In conclusion, combined treatment of RA (standard diet) andRB (diet with Swangi fish meal) increased (P<0.05) the size of muscle fiber diameter in majorpectorales and semimembranosus.